Understanding human resource management - Kamoche, Ken N. (Buckingham : Open University Press, 2001)
This book critically examines contemporary issues in the management of people. It reviews some of the significant themes that have shaped HRM as it has emerged during the course of the last century and identifies the definitive role of the tension between the drive for organizational performance and the 'humanization' of work.
The HRM debate: a reappraisal -- The emergence of "strategic HRM" -- The contribution of the resource-based view -- The dynamics of appropriation -- Knowledge management -- an emergent paradigm -- International HRM -- Managing in a social context -- The future of HRM
Includes bibliographical references.
Keywords: HUMAN RESOURCE MANAGEMENT